Leukemia inhibitory factor receptor homodimerization mediated by acetylation of extracellular lysine promotes prostate cancer progression through the PDPK1/AKT/GCN5 axis. Issue 2 (16th February 2022) - Ding, Yufeng; Chi, Honggang; Shao, Jialiang; Shi, Tiezhu; Yu, Hua; Wang, Xiang; Wang, Xiongjun
Abstract: Background: Prostate cancer (PCa), an inert tumour, has a long progression period, but valid biomarkers and methods for effectively and sensitively monitoring PCa progression are lacking, prompting us to identify new predictors for diagnosis and prognosis. Posttranslational modifications characterizing receptor activation are considered potentially strong indicators of disease progression. Methods: The posttranscriptional regulation of leukaemia inhibitory factor receptor (LIFR) and its novel downstream signalling activity in PCa were studied using liquid mass spectrometry, genetically engineered mouse (GEM) models, organoid assays, lentivirus packaging, infection and stable cell line construction. Results: In this study, the level of acetylated K620 on LIFR in its extracellular domain was shown to predict the progression and prognosis of PCa. In PCa cells, LIFR‐K620 acetylation is reversibly mediated by GCN5 and SIRT2. GEM experiments and organoid assays confirmed that the loss of LIFR‐K620 acetylation inhibits PCa progression. Mechanistically, K620 acetylation facilitates LIFR homodimerization and subsequently promotes LIFR‐S1044 phosphorylation and activation, which further recruits PDPK1 to activate AKT signalling and sequentially enhances the GCN5 protein level to sustain the protumour level of LIFR‐K620 acetylation by preventing GCN5 degradation via CRL4 Cdt2 E3 ligase. Conclusions: Acetylation of extracellular K620 on LIFR reinforces its homodimerization and integrates the activities of PDPK1, AKT, GSK3β and GCN5 to form a novel positive feedback loop in PCa; this modification is thus a promising biomarker for monitoring PCa progression. Abstract : We first demonstrated that LIFR homodimer formation mediated by K620 acetylation is upregulated in the prostate epithelium in an AKT‐dependent manner and is indispensably required for the malignancy of PTEN‐null tumors. Based on this study, the acetylation of LIFR‐K620 can be used as a biomarker for prognosis in prostate cancer patients for non‐invasive testing, and also as a potential therapeutic target.